2001
DOI: 10.1067/mtc.2001.114099
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral injury during cardiopulmonary bypass: Emboli impair memory

Abstract: Cognitive deficits were common after cardiopulmonary bypass. Occult cerebrovascular disease was more severe than expected and predisposed to attention difficulties, whereas emboli caused memory deficits. We believe this to be the first report of differing cognitive effects from emboli and hypoperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
113
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(126 citation statements)
references
References 42 publications
7
113
1
5
Order By: Relevance
“…Even the patient with the highest embolic count (Ͼ500) was discharged with no detectable cognitive dysfunction. 6 The early concern regarding microembolism to the brain during cardiac surgery being a cause of postoperative cognitive dysfunction 26,27 has not been confirmed in more recent studies 28 and systematic reviews. 29,30 Liu et al 31 reported a median embolic count of 430 (range, 155-2088) in patients undergoing cardiac surgery with cardiopulmonary bypass against a median embolic count of 2 (range, 0 -66) in off-pump surgery but could show no difference in cognitive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Even the patient with the highest embolic count (Ͼ500) was discharged with no detectable cognitive dysfunction. 6 The early concern regarding microembolism to the brain during cardiac surgery being a cause of postoperative cognitive dysfunction 26,27 has not been confirmed in more recent studies 28 and systematic reviews. 29,30 Liu et al 31 reported a median embolic count of 430 (range, 155-2088) in patients undergoing cardiac surgery with cardiopulmonary bypass against a median embolic count of 2 (range, 0 -66) in off-pump surgery but could show no difference in cognitive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…To date, studies examining associations between surgery and delirium have investigated microemboli migration [149][150][151], hypoperfusion [64,137,[152][153][154], inflammatory responses [155][156][157], changes in hormone levels [158][159][160][161], and local and general anesthesia [64,133,162,163]. Gottesman and colleagues [152] hypothesized that a drop in the mean arterial pressure may put patients at risk for early cognitive dysfunction.…”
Section: Surgical Factors and Postoperative Cognitive Dysfunctionmentioning
confidence: 99%
“…43 A study with patients submitted to heart surgery demonstrated that hypoperfusion during the procedure was related to attention deficit. 35 This finding is also of relevance to patients undergoing carotid revascularization procedures, since these operations also involve a certain degree of hypoperfusion.…”
Section: Hemodynamic Changes and Repercussions For Cognitive Functionmentioning
confidence: 90%
“…26,35 By extrapolation, this finding might also be of relevance to carotid revascularization patients.…”
Section: 2829mentioning
confidence: 99%